Analysis of signalized intersections with varied traffic conditions - Navata, Mark Paolo P.; Valdez, Adrian Roy L.; Villano, Joshua Martin M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Severe traffic congestion in city is a common problem nowadays. Numerous solutions have been implemented by different government agencies but most of the time, protracted over years of construction and litigation. Optimizing traffic light duration, however, has less social and legal considerations. This study poses the problem of finding the optimal way of improving traffic light or intersection systems through modeling actual and possible scenarios. This study on vehicular traffic is focused on signalized intersections wih changes to variables such as traffic light durations, volume flow, exit rate, and road lengths.
Thesis (B.S. Computer Science)--University of the Philippines Diliman
Keywords: Traffic engineering -- Mathematical models; Agent-based modeling (ABM).